Implementasi E-Government Aplikasi Integrasi Pupuk Bersubsidi (Ipubers) Dalam Pengoptimalan Distribusi Pupuk Bersubsidi Di Kecamatan Lima Kaum - Amanda, Alia; Sasmita, Siska (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research is driven by problems related to subsidized fertilizer distribution that is not in accordance with the right principle (right amount, type, time, place, quality and price). This encourages a change in the distribution of subsidized fertilizers called iPubers. Therefore, this research wants to see how the implementation of iPubers in the perspective of E-Government. This research aims to find out how the implementation of E-Government Subsidized Fertilizer Integration Application (iPubers) in optimizing the distribution of subsidized fertilizers. This research employs a qualitative method with a descriptive approach. The data is collected through interviews, observations and documentation studies. The research findings show that the procurement and distribution of subsidized fertilizers follow several stages, namely: a) planning and procurement of subsidized fertilizers, b) distribution and redemption of subsidized fertilizers through the iPubers application, c) receipt of subsidized fertilizers by farmers through the iPubers application, d) reporting and supervision of subsidized fertilizers. The results of this study refer to Indrajit's notion of six important components that must be considered in implementing E-Government, namely: 1) content development, 2) competency building, 3) connectivity, 4) cyber laws, 5) citizen interfaces, 6) capital is not applied thoroughly in the iPubers application. Therefore, application development and training for retailers and farmers are needed.